Analisis Pengaruh Kebijakan Investasi, Pertumbuhan Penjualan Dan Efisiensi Biaya Operasi Terhadap Profitabilitas - Supriadi, Yoyon; Syahidah, Hafsah (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
The purposes of this research was to analyze investment policy, the growth in sales, and operational cost efficiency to profitability of PT. Gudang Garam Tbkand PT. Ultrajaya Milk Industry & Trading Tbk. The type and source of data that used by the author are secondary data derived from the company's official website and the Indonesia Stock Exchange (www.idx.co.id). To obtain partial and simultaneous variables’ influence, analytical method was being applied. Thepartially regression analysis results for the case of PT Gudang Garam Tbk. indicates that investment policy and operational cost efficiency were not significantly affecting the company's profitability (ROA), and the growth in sales was significantly affecting the company's profitability (ROA). While simultaneously regression analyses (on investment policy and growth in sales) were not significantly affecting the company's profitability (ROA). In the case of PT. Ultrajaya Mil Industry & Trading Company, Tbk. the contradicting results were obtained, where the investment policy and operational cost efficiency were significantly affecting the company's profitability (ROA), and growth in sales was not significantly affecting the company's profitability (ROA). Simultaneously, investment policy and growth in sale), growth in sales and operational cost efficiency, were not significantly affecting the company's profitability (ROA)